2003
DOI: 10.1021/bi026949a
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human and Mouse Hepatic Scavenger Receptor Class B Type I (SR-BI) in the Selective Uptake of Low-Density Lipoprotein−Cholesteryl Esters

Abstract: Low-density lipoprotein (LDL)-cholesteryl ester (CE) selective uptake has been demonstrated in nonhepatic cells overexpressing the scavenger receptor class B type I (SR-BI). The role of hepatic SR-BI toward LDL, the main carrier of plasma CE in humans, remains unclear. The aim of this study was to determine if SR-BI, expressed at its normal level, is implicated in LDL-CE selective uptake in human HepG2 hepatoma cells and mouse hepatic cells, to quantify its contribution and to determine if LDL-CE selective upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 73 publications
1
35
1
Order By: Relevance
“…We found that SR-BI is recovered in Triton X-100 soluble fractions of HepG2 cells (Rhainds et al, 2003). It is worth noting that a concentration of Triton X-100 as low as 0.25% was sufficient to solubilize >80% of SR-BI in HepG2 cells and that SR-BI in the Triton X-100 insoluble fraction was detectable only in HepG2 cells extracted with 0.1% Triton X-100 (data not shown).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…We found that SR-BI is recovered in Triton X-100 soluble fractions of HepG2 cells (Rhainds et al, 2003). It is worth noting that a concentration of Triton X-100 as low as 0.25% was sufficient to solubilize >80% of SR-BI in HepG2 cells and that SR-BI in the Triton X-100 insoluble fraction was detectable only in HepG2 cells extracted with 0.1% Triton X-100 (data not shown).…”
Section: Discussionmentioning
confidence: 72%
“…Our results show that CE selective uptake from LDL, which is a SR-BI-dependent pathway in HepG2 cells Rhainds et al, 2003), was sensitive to enzymatic disruption of rafts structure by either COase, SMase or to sequestration of membrane cholesterol by filipin III treatment. Surprisingly, CE selective uptake from HDL3 increased with COase, SMase and β-CD.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…28 To establish whether scavenger receptors are involved, we incubated the hepatocyte-LSEC cocultures with a fivefold excess of unlabelled acLDL (100 g/mL). Figure 2A shows that the addition of acLDL did not interfere with the internalization of DiI-LDL by hepatocytes in cocultures, suggesting that the hepatic scavenger cell receptors are not involved in the upregulation of LDL uptake.…”
Section: Ldl Uptake In Hepatocyte Culture and Coculturementioning
confidence: 99%